Crespa ou alisada: os diferentes significados da manipulação do cabelo afro entre mulheres negras da cidade de Santa Maria – RS - Pires, Karen Tolentino de (2015)
This study covers the hair of black women in the city of Santa Maria / RS as a diacritical mark of blackness. It is an ethnographic study in two environments: the Angelita‟s beauty saloon and the Treze de Maio Museum, the first prevail straightened hair and the second the curly hair. The work is mainly aimed to analyze the different meanings the different ways of african hair manipulation: smoothing, relaxing, African permanent hair extensions, Nago braids and natural curly. Through this research it is clear that such a choice is linked to the multiple identities and social environments experienced by these women: The Treze de Maio museum, the Carnival, the "ballads", and feasts. In the first case it was found that women undergo a "ritual of afrianization and especially in the latter case, largely, there is a lessening of blackness. Are also taken representations associated with that choice such as good looks for work and loving relationships. It was also found that the generation is an important variable to understand the choice determined by capillary handling, for older women undergo a major face to use your natural hair and, on the other hand, for younger, makes it easier for assumed it. The fact that younger women are more open to take its natural curly is because of experiencing a moment of appreciation of blackness. This process can be understood by the performance of black activist movements, re-africanization process and exaltation of the African "roots", by affirmative action policies, among other elements.